Asymmetric composite solid electrolyte and preparation method thereof

CN119764552AActive Publication Date: 2025-04-04JIANGSU UNIV OF SCI & TECH

Patent Information

Application Number
CN202510204320.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-04
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The solid electrolytes of existing solid-state lithium metal batteries have problems such as low ionic conductivity, poor flexibility and low mechanical strength, which hinder their practical application.

Method used

Using an asymmetric composite solid electrolyte structure, a bilayer structure is formed by uniformly dispersing the Li-IL@Cu-BTC ion conductor and the PVDF-HFP matrix in the first and second electrolyte layers to form a double-layer structure to improve the ionic conductivity and mechanical properties of the electrolyte.

Benefits of technology

It achieves high ionic conductivity and excellent mechanical properties, which can effectively inhibit the growth of lithium dendrites, reduce the risk of battery short circuit, and improve the cycle stability and reversible capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764552A_ABST
    Figure CN119764552A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric composite solid electrolyte and a preparation method thereof, the asymmetric composite solid electrolyte comprises a first electrolyte layer and a second electrolyte layer, and the second electrolyte layer is arranged on the first electrolyte layer; the first electrolyte layer comprises 75 to 85 weight percent of Li-IL (at) Cu-BTC and 15 to 25 weight percent of PVDF-HFP (Polyvinylidene Fluoride-Hexafluoropropylene), and the second electrolyte layer comprises 15 to 25 weight percent of Li-IL (at) Cu-BTC and 75 to 85 weight percent of PVDF-HFP; and the Li-IL is packaged in a Cu-BTC pore channel. The room-temperature ionic liquid disclosed by the invention shows high ionic conductivity, high thermal stability and environmental friendliness, and modifies an MOF pore channel to form a Li-IL-coated Cu-BTC ionic conductor; the high-content Li-IL-coated Cu-BTC ion conductor shortens the lithium ion transmission distance and is compactly stacked on the cathode side, and a continuous lithium ion transmission path is established.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolyte and a preparation method thereof, in particular to an asymmetric composite solid electrolyte and a preparation method thereof. Background Art

[0002] Traditional lithium-ion batteries are widely used in computers, mobile phones, electric vehicles, energy storage power stations and other fields due to their inherent advantages such as high energy density, long cycle life, no memory effect and easy portability. However, the energy density of commercial lithium-ion batteries has reached its limit, and leakage of organic electrolytes can easily lead to battery short circuits and explosions, causing safety issues such as fire. Therefore, solid-state lithium metal batteries using solid-state electrolytes are considered to be an effective strategy to meet people's growing demand for high-safety, high-energy-density energy storage devices. However, solid-state electrolytes face problems such as low ionic conductivity, poor flexibility, and low mechanical strength, which hinder the practical application of solid-state electrolytes.

[0003] Solid electrolytes can be divided into inorganic solid electrolytes, organic solid electrolytes and composite solid electrolytes. Inorganic solid electrolytes have high ionic conductivity, but they are not in sufficient contact with the electrodes and have large interface impedance. Organic solid electrolytes have the advantages of good flexibility, low cost, and easy processing, but their ionic conductivity is relatively low. Composite solid electrolytes combine the advantages of inorganic and organic solid electrolytes and effectively solve the problems of the two types of electrolytes. The ionic conductivity of pure polymer electrolytes is very low (usually <10 at room temperature). -6 S cm -1 ), by using imidazolium-type ionic liquids (Li-IL) and other materials to modify the surface chemically of MOF, as a functional filler, the ionic conductivity and electrochemical properties of polymer electrolytes can be improved. The introduction of MOF can reduce the crystallinity of the polymer, and its porous structure can also serve as an ion transport channel, but the improvement of ionic conductivity by doping a small amount of MOF particles is limited. In addition, the addition of a small amount of MOF filler to the polymer matrix can improve the mechanical strength of the composite electrolyte. In general, the excellent mechanical strength and flexibility of the composite electrolyte can physically inhibit lithium dendrites. However, there is a negative correlation between the ionic conductivity and mechanical strength of most polymer-based composite solid electrolytes, which makes it challenging to simultaneously improve mechanical properties and ionic conductivity.

[0004] Therefore, there is an urgent need to construct novel microstructured polymer composite electrolytes to precisely control ionic conductivity and improve lithium dendrite suppression capabilities, respectively. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an asymmetric composite solid electrolyte with flexibility and high ionic conductivity. Another purpose of the present invention is to provide a method for preparing an asymmetric composite solid electrolyte that can be precisely controlled, environmentally friendly and convenient.

[0006] Technical solution: The asymmetric composite solid electrolyte described in the present invention includes a first electrolyte layer and a second electrolyte layer, and the second electrolyte layer is arranged on the first electrolyte layer; the first electrolyte layer includes 75-85wt% Li-IL@Cu-BTC and 15-25wt% PVDF-HFP, and the second electrolyte layer includes 15-25wt% Li-IL@Cu-BTC and 75-85wt% PVDF-HFP; the Li-IL in Li-IL@Cu-BTC is encapsulated in the pores of Cu-BTC.

[0007] Furthermore, the Li-IL@Cu-BTC in the first electrolyte layer and the second electrolyte layer are uniformly dispersed in PVDF-HFP.

[0008] Furthermore, the thickness of the first electrolyte layer is 28-32 μm, and the thickness of the second electrolyte layer is 7-10 μm.

[0009] The method for preparing the asymmetric composite solid electrolyte of the present invention comprises the following steps:

[0010] Step 1, respectively preparing methanol solutions of 1,3,5-benzenetricarboxylic acid, copper nitrate trihydrate and polyvinyl pyrrolidone, mixing them evenly, standing them for aging, then collecting the samples by centrifugation, washing them with methanol for multiple times, vacuum drying the Cu-BTC, and grinding them into powder;

[0011] Step 2: In an argon glove box, LiTFSI was dissolved in 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]) to prepare Li-IL, and the mixture was stirred evenly. Li-IL and Cu-BTC were ground and mixed evenly, and heated under vacuum conditions to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder.

[0012] Step 3, dispersing Li-IL@Cu-BTC powder in N-methylpyrrolidone solvent, stirring to form a suspension, and then adding LiTFSI and PVDF-HFP particles respectively, and performing uniform magnetic stirring to obtain a first electrolyte layer slurry and a second electrolyte layer slurry respectively;

[0013] Step 4: coating the first electrolyte layer slurry on a glass plate, vacuum drying to obtain a first electrolyte layer, and then coating the second electrolyte layer slurry on the first electrolyte layer, vacuum drying to obtain an asymmetric composite solid electrolyte membrane.

[0014] Further, in step 1, the concentration of 1,3,5-benzenetricarboxylic acid in the methanol solution of 1,3,5-benzenetricarboxylic acid is 0.04-0.1 mol / L, the concentration of copper nitrate trihydrate in the methanol solution of copper nitrate trihydrate is 0.06-0.1 mol / L, and the mass ratio of copper nitrate trihydrate to PVP is 1:0.2-0.5. The temperature of static aging is 25-30°C, and the time is 24-36 hours.

[0015] Further, in step 2, the mass ratio of LiTFSI to 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide is 1:4-6, and the mass ratio of Li-IL to Cu-BTC is 1-2:1. Li-IL is vacuum dried at 110-120°C for 12-24 hours before use, and Cu-BTC is vacuum dried at 150-160°C for 8-12 hours before use.

[0016] Furthermore, in step three, the mass ratio of PVDF-HFP to LiTFSI is 1 to 5:1.

[0017] Furthermore, in step 4, vacuum drying is performed by stepwise heating within a range of 30 to 60°C.

[0018] Preparation principle: The functional filler Li-IL@Cu-BTC is obtained by encapsulating ionic liquid in the pore structure of Cu-BTC, and then adding it to the PVDF-HFP-based solid electrolyte. The Li-IL@Cu-BTC polymer solid electrolyte with different mass ratios is coated layer by layer. The double-layer structure makes the composite solid electrolyte have excellent mechanical properties and good ionic conductivity. The Li-IL@Cu-BTC ion conductor can also uniformly guide the deposition / stripping of lithium ions. The double-layer coating design can adapt the cathode and anode according to the different characteristics of the Li-IL@Cu-BTC ion conductor content in the matrix. The high-content Li-IL@Cu-BTC ion conductor on the cathode side is densely stacked, shortening the lithium ion transmission distance, establishing a continuous lithium ion transport path, showing good ionic conductivity, and improving the cathode activity and stability. The low-content Li-IL@Cu-BTC polymer matrix thin layer on the anode side has a thickness of only 8.1μm, which reduces the adverse effect on the overall ionic conductivity of the membrane, shows excellent mechanical properties, and well hinders the growth of lithium dendrites, reducing the risk of battery short circuit. The asymmetric ion conductor content double-layer structure has the same transport mechanism and synergistic complementary effect on both sides, which makes the composite solid-state lithium metal battery have good cycle stability and high reversible capacity.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0020] 1. Room temperature ionic liquids exhibit high ionic conductivity, high thermal stability and are environmentally friendly, modifying MOF pores to form Li-IL@Cu-BTC ion conductors;

[0021] 2. The high content of Li-IL@Cu-BTC ion conductor shortens the transmission distance of lithium ions, densely accumulates on the cathode side, and establishes a continuous lithium ion transport path;

[0022] 3. The high-content Li-IL@Cu-BTC layer exhibits good ionic conductivity and can improve cathode activity and stability;

[0023] 4. The low-content Li-IL@Cu-BTC polymer matrix thin layer on the anode side has a thickness of only 8.1 μm, which reduces the adverse effect on the overall ionic conductivity of the membrane, exhibits excellent mechanical properties, and effectively hinders the growth of lithium dendrites, reducing the risk of battery short circuit;

[0024] 5. The asymmetric structure makes the composite solid electrolyte flexible and has high ionic conductivity, with an overall thickness of only 38.4μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The surface morphology and cross-sectional SEM images of the 20% Li-IL@Cu-BTC side and the 80% Li-IL@Cu-BTC side of the asymmetric composite solid electrolyte in Example 1, wherein a) is a SEM image of the second electrolyte layer, b) is a SEM image of the first electrolyte layer, c) is a SEM image of the cross section of the first electrolyte layer, and d) is a SEM image of the cross section of the second electrolyte layer;

[0026] Figure 2 It is a bar graph of tensile strength and Young's modulus of Example 1, Comparative Example 2 and Comparative Example 4;

[0027] Figure 3 1 is the stress-strain curve of Example 1, Comparative Example 2 and Comparative Example 4;

[0028] Figure 4 Graphs of ionic conductivity of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4;

[0029] Figure 5 The results of Example 1, Comparative Example 2 and Comparative Example 4 at room temperature 0.1 mA cm -2 Cycling performance diagram of lithium symmetric battery under conditions;

[0030] Figure 6 It is a long cycle performance diagram of the lithium metal battery of Example 1, Comparative Example 2 and Comparative Example 4 at room temperature 0.5C. DETAILED DESCRIPTION

[0031] The materials, reagents, instruments, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods in the examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. 1-Ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt (EMIMTFSI, 99%), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, 99.9%), 1-methyl-2-pyrrolidone (NMP, 99.9%), trimesic acid, polyvinylpyrrolidone, copper nitrate, poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) were purchased from MacLean.

[0032] Example 1

[0033] A method for preparing an asymmetric composite solid electrolyte comprises the following steps:

[0034] (1) Prepare 125 mL of 0.066 mol / L copper nitrate trihydrate methanol solution, disperse 1 g of PVP in the above solution, and record it as solution A. Prepare 125 mL of 0.042 mol / L 1,3,5-benzenetricarboxylic acid methanol solution, and record it as solution B. Add solution B dropwise into solution A, let stand at 25°C for 24 h, collect the blue product by centrifugation, wash it with methanol three times, dry it at 80°C for 12 h, and grind it into powder to prepare Cu-BTC.

[0035] (2) Li-IL was dried under vacuum at 120°C for 12 hours before use to remove moisture. In an argon glove box, 1 g of LiTFSI was dissolved in 5.46 g of [EMIM][TFSI] to prepare Li-IL, and the mixture was stirred at 30°C.

[0036] (3) Weigh 1g of Cu-BTC powder and activate it in vacuum at 160℃ for 8 hours. Add 2g of Li-IL to the activated Cu-BTC powder, grind and mix evenly, and heat it at 120℃ under vacuum for 12h to make Li-IL enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder. Cu-BTC has a multi-level microporous structure with pore sizes mainly distributed between 0.5 and 0.8nm, ensuring that the EMIMs with sizes of 0.79 and 0.76nm are + and TFSI - Able to enter the pores, where micropores smaller than 0.7 nm hinder EMIM + and TFSI - migration, while allowing Li + (0.076nm) can move freely, so that the composite solid electrolyte membrane can obtain a higher lithium ion migration number.

[0037] (4) The Li-IL@Cu-BTC powder was dispersed in NMP solvent and stirred to form a suspension. Then, LiTFSI and PVDF-HFP particles were added in a mass ratio of 1:4, respectively, and the mixture was magnetically stirred at a uniform speed for 24 h to obtain the first electrolyte layer slurry and the second electrolyte layer slurry, respectively.

[0038] (5) The first electrolyte layer slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40°C and 50°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a first electrolyte layer. The second electrolyte layer slurry is evenly coated on the first electrolyte layer with a scraper, placed in a vacuum drying oven and heated at 40°C and 50°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a second electrolyte layer, that is, an asymmetric composite solid electrolyte membrane.

[0039] The first electrolyte layer of the obtained composite solid electrolyte membrane includes 80wt% Li-IL@Cu-BTC and 20wt% PVDF-HFP, with a thickness of 30.3μm. The second electrolyte layer includes 20wt% Li-IL@Cu-BTC and 80wt% PVDF-HFP, with a thickness of 8.1μm. Li-IL@Cu-BTC is uniformly dispersed in PVDF-HFP.

[0040] Comparative Example 1

[0041] LiTFSI and PVDF-HFP particles were added to NMP solvent and magnetically stirred at a constant speed for 24 hours, wherein the mass ratio of PVDF-HFP to LiTFSI was 4:1. The slurry was evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40 and 50 °C for 2 hours, and then vacuum dried at 60 °C for 24 hours to obtain a composite solid electrolyte membrane.

[0042] Comparative Example 2

[0043] Step (1), prepare 125mL of 0.066mol / L methanol solution of copper nitrate trihydrate, disperse 1g of PVP in the above solution, and record it as solution A. Prepare 125mL of 0.042mol / L methanol solution of benzenetricarboxylic acid, and record it as solution B. Add solution B dropwise to solution A, let stand at room temperature for 24h, collect the blue product by centrifugation, wash it with methanol 3 times, dry it at 80°C for 12h, and grind it into powder to prepare Cu-BTC.

[0044] Step (2), weigh 1 g of lithium bis(trifluorosulfonyl)imide (LiTFSI) in an argon glove box, dissolve it in 5.46 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI) ionic liquid to prepare Li-IL, stir it evenly at 30°C, and dry it in vacuum at 120°C to remove moisture before use.

[0045] Step (3), weigh 1 g of Cu-BTC powder and activate it in vacuum at 160 ° C for 8 h, add 2 g of Li-IL to the activated MOFs, grind and mix evenly, and heat at 120 ° C for 12 h under vacuum conditions to allow Li-IL to fully enter the Cu-BTC pores to prepare Li-IL@Cu-BTC powder.

[0046] Step (4), dispersing Li-IL@Cu-BTC in NMP solvent, stirring to form a suspension, then adding LiTFSI and PVDF-HFP respectively, and performing uniform magnetic stirring for 24 hours, wherein the mass ratio of PVDF-HFP to LiTFSI in the above process is 4:1. The above slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40 and 50 ° C for 2 hours, and then vacuum dried at 60 ° C for 24 hours to obtain a composite solid electrolyte membrane. The mass ratio of Li-IL@Cu-BTC in the solid electrolyte is 20%.

[0047] Comparative Example 3

[0048] Step (1), prepare 125mL of 0.066mol / L methanol solution of copper nitrate trihydrate, disperse 1g of PVP in the above solution, and record it as solution A. Prepare 125mL of 0.042mol / L methanol solution of benzenetricarboxylic acid, and record it as solution B. Add solution B dropwise to solution A, let stand at room temperature for 24h, collect the blue product by centrifugation, wash it with methanol 3 times, dry it at 80°C for 12h, and grind it into powder to prepare Cu-BTC.

[0049] Step (2), weigh 1 g of lithium bis(trifluorosulfonyl)imide (LiTFSI) in an argon glove box, dissolve it in 5.46 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI) ionic liquid to prepare Li-IL, stir it evenly at 30°C, and dry it in vacuum at 120°C to remove moisture before use.

[0050] Step (3), weigh 1 g of Cu-BTC powder and activate it in vacuum at 160 ° C for 8 h, add 2 g of Li-IL to the activated MOFs, grind and mix evenly, and heat at 120 ° C for 12 h under vacuum conditions to allow Li-IL to fully enter the Cu-BTC pores to prepare Li-IL@Cu-BTC powder.

[0051] Step (4), dispersing Li-IL@Cu-BTC in NMP solvent, stirring to form a suspension, then adding LiTFSI and PVDF-HFP respectively, and performing uniform magnetic stirring for 24 hours, wherein the mass ratio of PVDF-HFP to LiTFSI in the above process is 4:1. The above slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40 and 50 ° C for 2 hours, and then vacuum dried at 60 ° C for 24 hours to obtain a composite solid electrolyte membrane. The mass ratio of Li-IL@Cu-BTC in the solid electrolyte is 50%.

[0052] Comparative Example 4

[0053] Step (1), prepare 125mL of 0.066mol / L methanol solution of copper nitrate trihydrate, disperse 1g of PVP in the above solution, and record it as solution A. Prepare 125mL of 0.042mol / L methanol solution of benzenetricarboxylic acid, and record it as solution B. Add solution B dropwise to solution A, let stand at room temperature for 24h, collect the blue product by centrifugation, wash it with methanol 3 times, dry it at 80°C for 12h, and grind it into powder to prepare Cu-BTC.

[0054] Step (2), weigh 1 g of lithium bis(trifluorosulfonyl)imide (LiTFSI) in an argon glove box, dissolve it in 5.46 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI) ionic liquid to prepare Li-IL, stir it evenly at 30°C, and dry it in vacuum at 120°C to remove moisture before use.

[0055] Step (3), weigh 1 g of Cu-BTC powder and activate it in vacuum at 160°C for 8 h, add 2 g of Li-IL to the activated MOFs, grind and mix evenly, and heat at 120°C for 12 h under vacuum conditions to allow Li-IL to fully enter the Cu-BTC pores to prepare Li-IL@Cu.-BTC powder.

[0056] Step (4), dispersing Li-IL@Cu-BTC in NMP solvent, stirring to form a suspension, then adding LiTFSI and PVDF-HFP respectively, and performing uniform magnetic stirring for 24 hours, wherein the mass ratio of PVDF-HFP to LiTFSI in the above process is 4:1. The above slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40 and 50 ° C for 2 hours, and then vacuum dried at 60 ° C for 24 hours to obtain a composite solid electrolyte membrane. The mass ratio of Li-IL@Cu-BTC in the solid electrolyte is 80%.

[0057] Comparative Example 5

[0058] Step (1), prepare 125mL of 0.066mol / L methanol solution of copper nitrate trihydrate, disperse 1g of PVP in the above solution, and record it as solution A. Prepare 125mL of 0.042mol / L methanol solution of benzenetricarboxylic acid, and record it as solution B. Add solution B dropwise to solution A, let stand at room temperature for 24h, collect the blue product by centrifugation, wash it with methanol 3 times, dry it at 80°C for 12h, and grind it into powder to prepare Cu-BTC.

[0059] Step (2), weigh 1 g of lithium bis(trifluorosulfonyl)imide (LiTFSI) in an argon glove box, dissolve it in 5.46 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI) ionic liquid to prepare Li-IL, stir it evenly at 30°C, and dry it in vacuum at 120°C to remove moisture before use.

[0060] Step (3), weigh 1 g of Cu-BTC powder and activate it in vacuum at 160°C for 8 h, add 2 g of Li-IL to the activated MOFs, grind and mix evenly, and heat at 120°C for 12 h under vacuum conditions to allow Li-IL to fully enter the Cu-BTC pores to prepare Li-IL@Cu.-BTC powder.

[0061] Step (4), dispersing Li-IL@Cu-BTC in NMP solvent, stirring to form a suspension, then adding LiTFSI and PVDF-HFP respectively, and performing uniform magnetic stirring for 24 hours, wherein the mass ratio of PVDF-HFP to LiTFSI in the above process is 4:1. The above slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40 and 50 ° C for 2 hours, and then vacuum dried at 60 ° C for 24 hours to obtain a composite solid electrolyte membrane. The mass ratio of Li-IL@Cu-BTC in the solid electrolyte is 65%.

[0062] The solid electrolytes obtained in Example 1, Comparative Example 2, and Comparative Example 4 were assembled into a stainless steel symmetrical battery in an argon glove box to measure its ionic conductivity. In addition, the lithium deposition performance was measured by assembling a lithium symmetrical battery. The solid electrolytes obtained in Example 1, Comparative Example 2, and Comparative Example 3 were assembled into full batteries with LFP as the positive electrode and Li as the negative electrode to test the performance, with the side with a Li-IL@Cu-BTC mass ratio of 20% in contact with the lithium metal negative electrode and the side with a Li-IL@Cu-BTC mass ratio of 80% in contact with the LFP positive electrode.

[0063] like Figure 1The morphology and thickness of the Li-IL@Cu-BTC ion conductor of the asymmetric composite solid electrolyte at different content sides. When the mass ratio is 20%, a small amount of Li-IL@Cu-BTC filler improves the crystallinity of the pure PVDF-HFP polymer matrix, and the surface is smooth and uniform. When the mass ratio of Li-IL@Cu-BTC is 80%, a large number of MOF particles are densely stacked to form a continuous ion transmission channel.

[0064] like Figures 2-3 In the ionic conductivity test, Comparative Example 2 showed 1.77×10 -4 S cm -1 The ionic conductivity is significantly lower than that of Comparative Example 4 (4.08×10 -4 S cm -1 In addition, Example 1 has an ionic conductivity of 3.51×10 -4 S cm -1 The higher ionic conductivity ensures the rapid transmission of lithium ions in the solid electrolyte.

[0065] like Figure 4 , the mechanical properties of comparative example 2 are excellent, while the mechanical properties of comparative example 4 are very poor. In addition, the mechanical properties of embodiment 1 are greatly improved, which is better than comparative example 4.

[0066] like Figure 5 , Comparative Example 2 has the highest overpotential in lithium deposition, relying on good mechanical strength to inhibit dendrites from penetrating into the electrolyte, and the voltage increases until the battery necroses. Comparative Example 4 has the lowest overpotential, but is very prone to short circuit. The overpotential of Example 1 is low and remains stable, and can be stably cycled for 500h.

[0067] like Figure 6 The initial specific capacity of Example 2 is the lowest and decays rapidly. The initial specific capacity of Example 4 is higher, but also decays rapidly. The initial specific capacity of Example 1 is 140 mAh g -1 After 100 cycles, it can still reach 138.4 mAh g -1 The discharge specific capacity and cycle efficiency of 99.58% and the capacity retention rate reached 98.9%, indicating that the asymmetric double-layer structure design has a good balance between the ionic conductivity and mechanical strength of the composite solid electrolyte, showing good lithium metal battery performance.

[0068] Example 2

[0069] A method for preparing an asymmetric composite solid electrolyte comprises the following steps:

[0070] (1) Prepare 125 mL of 0.06 mol / L copper nitrate trihydrate methanol solution, disperse 0.8 g of PVP in the above solution, and record it as solution A. Prepare 125 mL of 0.04 mol / L 1,3,5-benzenetricarboxylic acid methanol solution, and record it as solution B. Add solution B dropwise into solution A, let stand at 25°C for 36 h, collect the blue product by centrifugation, wash it with methanol three times, dry it at 80°C for 12 h, and grind it into powder to prepare Cu-BTC.

[0071] (2) Li-IL was dried under vacuum at 110°C for 24 hours before use to remove moisture. In an argon glove box, 1 g of LiTFSI was dissolved in 4 g of [EMIM][TFSI] to prepare Li-IL, and the mixture was stirred at 30°C.

[0072] (3) 1 g of Cu-BTC powder was weighed and vacuum activated at 150 °C for 12 h. 1 g of Li-IL was added dropwise to the activated Cu-BTC powder, the mixture was ground and mixed evenly, and the mixture was heated at 120 °C under vacuum for 12 h to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder.

[0073] (4) The Li-IL@Cu-BTC powder was dispersed in NMP solvent and stirred to form a suspension. Then, LiTFSI and PVDF-HFP particles were added in a mass ratio of 1:1, respectively, and the mixture was magnetically stirred at a uniform speed for 24 h to obtain the first electrolyte layer slurry and the second electrolyte layer slurry, respectively.

[0074] (5) The first electrolyte layer slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 30°C and 40°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a first electrolyte layer. The second electrolyte layer slurry is evenly coated on the first electrolyte layer with a scraper, placed in a vacuum drying oven and heated at 30°C and 40°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a second electrolyte layer, that is, an asymmetric composite solid electrolyte membrane.

[0075] The first electrolyte layer of the obtained composite solid electrolyte membrane includes 75wt% Li-IL@Cu-BTC and 25wt% PVDF-HFP, with a thickness of 28μm. The second electrolyte layer includes 25wt% Li-IL@Cu-BTC and 75wt% PVDF-HFP, with a thickness of 7μm. Li-IL@Cu-BTC is uniformly dispersed in PVDF-HFP.

[0076] Example 3

[0077] A method for preparing an asymmetric composite solid electrolyte comprises the following steps:

[0078] (1) Prepare 125 mL of 0.1 mol / L methanol solution of copper nitrate trihydrate, and disperse 0.9 g of PVP in the above solution, which is recorded as solution A. Prepare 125 mL of 0.1 mol / L methanol solution of 1,3,5-benzenetricarboxylic acid, which is recorded as solution B. Add solution B dropwise to solution A, let stand at 30°C for 24 h, collect the blue product by centrifugation, wash it with methanol three times, dry it at 80°C for 12 h, and grind it into powder to prepare Cu-BTC.

[0079] (2) Li-IL was dried under vacuum at 120°C for 12 hours before use to remove moisture. In an argon glove box, 1 g of LiTFSI was dissolved in 5 g of [EMIM][TFSI] to prepare Li-IL, and the mixture was stirred at 30°C.

[0080] (3) 1 g of Cu-BTC powder was weighed and vacuum activated at 160 °C for 8 h. 2 g of Li-IL was added dropwise to the activated Cu-BTC powder, ground and mixed evenly, and heated at 120 °C under vacuum for 12 h to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder.

[0081] (4) The Li-IL@Cu-BTC powder was dispersed in NMP solvent and stirred to form a suspension. Then, LiTFSI and PVDF-HFP particles were added in a mass ratio of 1:5, respectively, and the mixture was magnetically stirred at a uniform speed for 24 h to obtain the first electrolyte layer slurry and the second electrolyte layer slurry, respectively.

[0082] (5) The first electrolyte layer slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 40°C and 50°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a first electrolyte layer. The second electrolyte layer slurry is evenly coated on the first electrolyte layer with a scraper, placed in a vacuum drying oven and heated at 40°C and 50°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a second electrolyte layer, that is, an asymmetric composite solid electrolyte membrane.

[0083] The first electrolyte layer of the obtained composite solid electrolyte membrane includes 85wt% Li-IL@Cu-BTC and 15wt% PVDF-HFP, with a thickness of 32μm. The second electrolyte layer includes 15wt% Li-IL@Cu-BTC and 85wt% PVDF-HFP, with a thickness of 10μm. Li-IL@Cu-BTC is uniformly dispersed in PVDF-HFP.

[0084] Example 4

[0085] A method for preparing an asymmetric composite solid electrolyte comprises the following steps:

[0086] (1) Prepare 125 mL of 0.08 mol / L copper nitrate trihydrate methanol solution, disperse 0.9 g of PVP in the above solution, and record it as solution A. Prepare 125 mL of 0.07 mol / L 1,3,5-benzenetricarboxylic acid methanol solution, and record it as solution B. Add solution B dropwise into solution A, let stand at 28°C for 30 h, collect the blue product by centrifugation, wash it with methanol three times, dry it at 80°C for 12 h, and grind it into powder to prepare Cu-BTC.

[0087] (2) Li-IL was dried under vacuum at 115°C for 18 hours before use to remove moisture. In an argon glove box, 1 g of LiTFSI was dissolved in 5 g of [EMIM][TFSI] to prepare Li-IL, and the mixture was stirred at 30°C.

[0088] (3) 1 g of Cu-BTC powder was weighed and vacuum activated at 155 °C for 10 h. 1.5 g of Li-IL was added dropwise to the activated Cu-BTC powder, ground and mixed evenly, and heated at 120 °C under vacuum for 12 h to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder.

[0089] (4) The Li-IL@Cu-BTC powder was dispersed in NMP solvent and stirred to form a suspension. Then, LiTFSI and PVDF-HFP particles were added in a mass ratio of 1:3, respectively, and the mixture was magnetically stirred at a uniform speed for 24 h to obtain the first electrolyte layer slurry and the second electrolyte layer slurry, respectively.

[0090] (5) The first electrolyte layer slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated at 35°C and 45°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a first electrolyte layer. The second electrolyte layer slurry is evenly coated on the first electrolyte layer with a scraper, placed in a vacuum drying oven and heated at 35°C and 45°C for 2 hours, and then vacuum dried at 60°C for 24 hours to obtain a second electrolyte layer, that is, an asymmetric composite solid electrolyte membrane.

[0091] The first electrolyte layer of the obtained composite solid electrolyte membrane includes 78wt% Li-IL@Cu-BTC and 22wt% PVDF-HFP, with a thickness of 30μm. The second electrolyte layer includes 22wt% Li-IL@Cu-BTC and 78wt% PVDF-HFP, with a thickness of 8μm. Li-IL@Cu-BTC is uniformly dispersed in PVDF-HFP.

[0092] Example 5

[0093] A method for preparing an asymmetric composite solid electrolyte comprises the following steps:

[0094] (1) Prepare 125 mL of 0.07 mol / L copper nitrate trihydrate methanol solution, disperse 1 g of PVP in the above solution, and record it as solution A. Prepare 125 mL of 0.08 mol / L 1,3,5-benzenetricarboxylic acid methanol solution, and record it as solution B. Add solution B dropwise into solution A, let stand at 28°C for 26 h, collect the blue product by centrifugation, wash it with methanol three times, dry it at 80°C for 12 h, and grind it into powder to prepare Cu-BTC.

[0095] (2) Li-IL was vacuum dried at 112°C for 20 hours before use to remove moisture. In an argon glove box, 1 g of LiTFSI was dissolved in 5 g of [EMIM][TFSI] to prepare Li-IL, and the mixture was stirred at 30°C.

[0096] (3) 1 g of Cu-BTC powder was weighed and vacuum activated at 158 ​​°C for 9 h. 1 g of Li-IL was added dropwise to the activated Cu-BTC powder, the mixture was ground and mixed evenly, and heated at 120 °C under vacuum for 12 h to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder.

[0097] (4) The Li-IL@Cu-BTC powder was dispersed in NMP solvent and stirred to form a suspension. Then, LiTFSI and PVDF-HFP particles were added in a mass ratio of 1:4, respectively, and the mixture was magnetically stirred at a uniform speed for 24 h to obtain the first electrolyte layer slurry and the second electrolyte layer slurry, respectively.

[0098] (5) The first electrolyte layer slurry is evenly coated on a glass plate with a scraper, placed in a vacuum drying oven and heated stepwise at 36°C and 47°C for 2 h, and then vacuum dried at 60°C for 24 h to obtain a first electrolyte layer. The second electrolyte layer slurry is evenly coated on the first electrolyte layer with a scraper, placed in a vacuum drying oven and heated stepwise at 36°C and 47°C for 2 h, and then vacuum dried at 60°C for 24 h to obtain a second electrolyte layer, that is, an asymmetric composite solid electrolyte membrane.

[0099] The first electrolyte layer of the obtained composite solid electrolyte membrane includes 81wt% Li-IL@Cu-BTC and 19wt% PVDF-HFP, with a thickness of 31μm. The second electrolyte layer includes 19wt% Li-IL@Cu-BTC and 81wt% PVDF-HFP, with a thickness of 9μm. Li-IL@Cu-BTC is uniformly dispersed in PVDF-HFP.

Claims

1. An asymmetric composite solid electrolyte, characterized in that: The invention comprises a first electrolyte layer and a second electrolyte layer, wherein the second electrolyte layer is arranged on the first electrolyte layer; the first electrolyte layer comprises 75-85wt% Li-IL@Cu-BTC and 15-25wt% PVDF-HFP, and the second electrolyte layer comprises 15-25wt% Li-IL@Cu-BTC and 75-85wt% PVDF-HFP; the Li-IL in the Li-IL@Cu-BTC is encapsulated in the pores of the Cu-BTC.

2. An asymmetric composite solid electrolyte according to claim 1, characterized in that: The Li-IL@Cu-BTC in the first electrolyte layer and the second electrolyte layer is uniformly dispersed in PVDF-HFP.

3. An asymmetric composite solid electrolyte according to claim 1, characterized in that: The thickness of the first electrolyte layer is 28-32 μm, and the thickness of the second electrolyte layer is 7-10 μm.

4. A method for preparing an asymmetric composite solid electrolyte according to claim 1, characterized in that: The following steps are involved: Step 1, respectively preparing methanol solutions of 1,3,5-benzenetricarboxylic acid, copper nitrate trihydrate and polyvinyl pyrrolidone, mixing them evenly, standing them for aging, then collecting the samples by centrifugation, washing them with methanol for multiple times, vacuum drying the Cu-BTC, and grinding them into powder; Step 2: In an argon glove box, LiTFSI was dissolved in 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide to prepare Li-IL, and the mixture was stirred evenly. Li-IL and Cu-BTC were ground and mixed evenly, and heated under vacuum conditions to allow Li-IL to enter the pores of Cu-BTC to form Li-IL@Cu-BTC powder. Step 3, dispersing Li-IL@Cu-BTC powder in N-methylpyrrolidone solvent, stirring to form a suspension, and then adding LiTFSI and PVDF-HFP particles respectively, and performing uniform magnetic stirring to obtain a first electrolyte layer slurry and a second electrolyte layer slurry respectively; Step 4: coating the first electrolyte layer slurry on a glass plate, vacuum drying to obtain a first electrolyte layer, and then coating the second electrolyte layer slurry on the first electrolyte layer, vacuum drying to obtain an asymmetric composite solid electrolyte membrane.

5. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 1, the concentration of 1,3,5-benzenetricarboxylic acid in the methanol solution of 1,3,5-benzenetricarboxylic acid is 0.04-0.1 mol / L, the concentration of copper nitrate trihydrate in the methanol solution of copper nitrate trihydrate is 0.06-0.1 mol / L, and the mass ratio of copper nitrate trihydrate to PVP is 1:0.2-0.

5.

6. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 1, the temperature of the static aging is 25 to 30° C. and the time is 24 to 36 hours.

7. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 2, the mass ratio of LiTFSI to 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide is 1:4-6, and the mass ratio of Li-IL to Cu-BTC is 1-2:

1.

8. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 2, Li-IL is vacuum dried at 110-120° C. for 12-24 hours before use, and Cu-BTC is vacuum dried at 150-160° C. for 8-12 hours before use.

9. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 3, the mass ratio of PVDF-HFP to LiTFSI is 1 to 5:

1.

10. The method for preparing an asymmetric composite solid electrolyte according to claim 4, characterized in that: In the step 4, vacuum drying is performed by stepwise heating within the range of 30 to 60°C.

Citation Information

Patent Citations

  • Preparation method of composite solid electrolyte based on metal organic framework / ionic liquid

    CN111180791A

  • Metal organic framework-polymer composite solid electrolyte as well as preparation method and application thereof

    CN113937363A

  • Multi-layer composite electrolyte membrane based on metal-organic framework material and preparation method of multi-layer composite electrolyte membrane

    CN115458807A

  • Asymmetric composite solid electrolyte membrane and preparation method and application thereof

    CN117712475A

  • Asymmetric composite electrolyte and preparation method and application thereof

    CN117936889A

Cited By

  • Preparation method and application of sulfide solid electrolyte membrane based on gradient polymer / ionic liquid composite binder, and all-solid-state battery

    CN120581677A